Long‐term outcome with focus on pulmonary hypertension in Obesity Hypoventilation Syndrome. (3rd July 2020) - Budweiser, Stephan; Tratz, Florian; Gfüllner, Florian; Pfeifer, Michael
Abstract: Introduction: Pulmonary Hypertension (PH) is a frequent comorbidity in Obesity Hypoventilation Syndrome (OHS). Objective: We investigated long‐term outcome of OHS with a particular emphasis on PH. Methods: In a prospective design, 64 patients with OHS and established noninvasive positive pressure ventilation (NPPV), were assessed by serum biomarkers, right heart catheterization, blood gases analysis, lung function, Epworth‐Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), World Health Organization‐functional class (WHO‐FC) and health‐related quality of life (HRQL) via the Severe Respiratory Insufficiency (SRI) questionnaire. After a planned follow‐up of 5 years patients were reassessed regarding vital status, WHO‐FC, ESS, SRI, PSQI, body mass index (BMI) and NPPV use. Prognostic markers were explored using univariate and multivariate Cox regression analyses. Results: At the 5‐year follow‐up, BMI tended to decrease ( P = 0.05), while WHO‐FC, ESS and PSQI remained unchanged. HRQL deteriorated in terms of SRI summary score and most subdomains ( P < .05 each). NPPV adherence still was high (89%), while daily NPPV use increased from 6.7 (5.1; 8.0) h/d to 8.2 (7.4; 9.0) h/d ( P < .05). After a 5‐year follow‐up, mortality was 25.8%. In univariate regression analyses only age > 69.5 years (HR = 4.145, 95%‐CI = 1.180‐14.565, P = 0.016), NT‐proBNP > 1256 pg/mL (HR = 5.162, 95%‐CI = 1.136‐23.467, P = 0.018), diffusion capacity for carbon monoxide (DLCO, %pred) (HR = 0.341, 95%‐CI = 0.114‐1.019, P = 0.043) and higher oxygen use during daytime (HR = 5.236, 95%‐CI = 1.489‐18.406, P = 0.004) predicted mortality. No independent factor predicting mortality was detected in multivariate analysis. Conclusion: Despite a high long‐term NPPV use HRQL worsened. Age, oxygen use at baseline, DLCO (%pred) and NT‐proBNP, as a surrogate parameter for PH, were related to long‐term survival.